Alcohol-preferring rats show decreased corticotropin-releasing hormone 2 receptor expression and differences in HPA activation compared to alcohol-nonpreferring rats - Yong, Weidong (2014)
BACKGROUND: Corticotropin releasing hormone (CRH) and urocortins (UCNs) bind to corticotropin releasing hormone type 2 receptor (CRH-R2), a Gs protein-coupled receptor that plays an important role in modulation of anxiety and stress responses. The Crhr2 gene maps to a quantitative trait locus (QTL) for alcohol preference on chromosome 4 previously identified in inbred alcohol-preferring (iP) and non-preferring (iNP) F2 rats. METHODS AND RESULTS: Crhr2 mRNA expression was determined in male alcohol-naïve iP and iNP rats in several brain regions, and lower levels of Crhr2 mRNA were observed in iP rats compared to iNP rats. To identify genetic variation that may underlie differences detected in Crhr2 expression, DNA sequencing was performed and variations were identified in the promoter region, coding region and 3’-untranslated region between the iP and iNP rats. A 7bp insertion in the Crhr2 promoter of iP rats altered expression in vitro as measured by reporter assays. While CRH-R2 binding affinity did not significantly differ between male iP and iNP receptor variants, CRH-R2 density was lower in the amygdala of iP as compared to iNP rats. Male P rats displayed decreased social interaction and significantly higher corticosterone levels directly following 30 minute restraint when compared to male NP rats. CONCLUSIONS: This study identified Crhr2 as a candidate gene of interest underlying the chromosome 4 QTL for alcohol consumption that was previously identified in the P and NP model. Crhr2 promoter polymorphism reduced mRNA expression in certain brain regions, particularly the amygdala, and lowered the density of CRH-R2 in the amygdala of iP compared to iNP rats. Together, these differences between the animals may contribute to the drinking disparity as well as the anxiety differences of the P and NP animals.